Technical Challenges in Current Primo Vascular System Research and Potential Solutions - Kyung A. Kang; Claudio Maldonado; Vitaly Vodyanoy (Medical Association of Pharmacopuncture Institute, 2016)
Since Bonghan Kim's discovery of the Bonghan system (BHS) in the 1960s, numerous reports have suggested that the system is fundamental for maintaining mammalian life. The BHS is a circulatory system independent of the blood or the lymphatic system, forms an extensive network throughout the entire mammalian body, has been reported to be the acupuncture meridian, stores distinct types of stem cells, and appears to have some roles in cancer metastasis. Despite Kim's first report having been published as early as 1962, research progress has been rather slow mainly because the system is very small and translucent, making it optically difficult to distinguish it from the hemoglobin-rich surrounding tissues. Unfortunately, Kim did not describe in detail the methods that he used for identifying and harvesting the system and the components of the system. In 2000, Kwang-Sup Soh reopened the BHS research, and since then, new and important scientific findings on the system have been reported, and many of Kim's results have been verified. In 2010, the BHS was renamed the primo vascular system. Nevertheless, good tools to properly deal with this system are still lacking. In this article, we address some of the technical difficulties involved in studying the primo vascular system and attempt to discuss potential ways to overcome those difficulties.